Validation of the Brazilian Oral Health Literacy-Adults Questionnaire - Eliete Rodrigues Almeida; Mohammad Mehdi Naghibi Sistani; Cristiane Baccin Bendo; Isabela de Almeida Pordeus; Ramon Targino Firmino; Saul Martins Paiva; Fernanda Morais Ferreira (SLACK Incorporated, 2022)
Background: Recognizing that a deficit of reading and numeracy skills is associated with poorer oral health, contemporary researchers have identified additional components as important attributes of oral health literacy (OHL). So, the use of comprehensive functional OHL tools is crucial. The Oral Health Literacy-Adults Questionnaire (OHL-AQ) evaluates reading comprehension, numeracy, listening and decision-making skills. Objective: Describe the validation process of the OHL-AQ Brazilian version (BOHL-AQ). Methods: The cross-culturally adapted version, BOHL-AQ, was applied to 180 employees age 18 to 71 years (mean = 37.2; standard deviation [SD] = 11.7) from a private university located in the Southeast of Brazil. Psychometric properties were evaluated through the analysis of internal consistency (Cronbach's alpha), reproducibility (test-retest), convergent validity (BREALD-30; education level), discriminant validity (family income; dental services), predictive validity (self-perception; literacy questions) and construct validity (Exploratory Factor Analysis). Confirmatory Factor Analysis (CFA) evaluated the dimensionality of the BOHL-AQ, with Promax method for rotation. Data were analyzed using SPSS Statistics software and the Mplus program. Key Results: BOHL-AQ mean score = 11.84 (SD = 3.1); administration mean time = 8 minutes (SD = 1.6); good internal reliability (Cronbach's alpha = 0.73) and excellent reproducibility (kappa = 0.89; intraclass correlation coefficient = 0.97). Preliminary tests showed that data were suitable for PCA (Kayser-Meyer-Olkin measure = 0.75; Barlett's Test of Sphericity significant [p < .001]). CFA showed that the instrument had a four-factor solution with excellent model fit estimates (χ2 = 636.587154.16, p value = .00117, Comparative Fit Index = 0.9787, Tucker Lewis index = 0.97, and Root Mean Square Error of the Approximation = 0.03). BOHL-AQ high scores significantly correlated to high education level, dental visit within the last year and for preventive reason, more independence and self-confidence on reading and filling out health forms, and better oral health self-perception (p < .05). Conclusions: The BOHL-AQ showed to be a fast and reliable instrument to assess a comprehensive functional OHL at Brazilian community and clinical settings. [HLRP: Health Literacy Research and Practice. 2022;6(3):e224-e231.] Plain Language Summary: Recognizing the need of advancing knowledge related to OHL, this study aimed to describe the validation process of the BOHL-AQ. Cross-cultural adaptation and psychometric properties evaluation presented satisfactory results. The BOHL-AQ proved to be a fast and valid instrument to measure comprehensive functional OHL in the Brazilian context.